Effectiveness of aspirin vs. clopidogrel in dogs with immune mediated haemolytic anaemia evaluated by serial thromboelastography and platelet mapping. (September 2022) - Griebsch, C.; Hall, E.; Barrs, V.R.
Abstract: Most dogs with immune mediated haemolytic anaemia (IMHA) are hypercoagulable, as measured by thromboelastography (TEG). Thromboelastography-platelet mapping (TEG-PM) has been used to assess platelet function in human patients treated with aspirin or clopidogrel. The aim of this study was to compare platelet thromboxane A 2 -receptor inhibition (TXA 2 - RI) and platelet adenosine diphosphate (ADP)-receptor inhibition (ADP-RI) as measured by TEG-PM in dogs with primary IMHA receiving aspirin or clopidogrel to determine if TEG-PM might be useful to monitor treatment. Eighteen client-owned dogs with IMHA were enroled in a prospective double blinded study. Dogs were randomised to receive aspirin or clopidogrel in addition to standard therapy. Thromboelastography was measured before, and 1 and 4 days after commencing treatment. Thromboelastography-PM was performed on days 1 and 4. Non-responders were defined as < 50 % platelet thromboxane A 2 -receptor inhibition (TXA 2 - RI) in the aspirin group and < 50 % platelet adenosine diphosphate (ADP)-receptor inhibition (ADP-RI) in the clopidogrel group, on day 4. Mean platelet TXA 2 -RI and platelet ADP-RI were not significantly different between groups at any timepoint ( P  > 0.05). The overall mean percentage inhibition of TXA2 -receptor was 25 % (aspirin 33 %, clopidogrel 15 %), and of ADP-receptor was 82 % (aspirin 83 %, clopidogrel 80 %). On day 4, 6/9 dogs (66 %) in the aspirin group and 2/8 dogs (25 %) in the clopidogrel group were non-responders ( P  = 0.086). Two dogs defined as responders based on TEG-PM developed thromboembolism. Overall, there was no significant difference in efficacy between aspirin and clopidogrel based on measurement of receptor inhibition using TEG-PM ( P  > 0.05), and routine TEG was not reliable for monitoring treatment response in dogs with IMHA. In some dogs, there was a discrepancy between TEG-PM results and clinical response. Further investigation of TEG-PM use in dogs, including its usefulness to monitor treatment response and adjust treatment in individual dogs and any effect of anaemia, is warranted. Highlights: Thromboelastography-platelet mapping (TEG-PM) was useful to monitor thrombophylaxis. There was no significant difference in efficacy between aspirin and clopidogrel. TEG-PM detected non-responders and could guide dose adjustments. TEG-PM could be useful to tailor thrombophylactic therapy in individual dogs.